Hypofunctional Dopamine Uptake and Antipsychotic Treatment-Resistant Schizophrenia - Amato, Davide; Kruyer, Anna; Samaha, Anne-Noël; Heinz, Andreas (Frontiers in Psychiatry, 2019)
Antipsychotic treatment resistance in schizophrenia remains a major issue in psychiatry. Nearly 30% of patients with schizophrenia do not respond to antipsychotic treatment, yet the underlying neurobiological causes are unknown. All effective antipsychotic medications are thought to achieve their efficacy by targeting the dopaminergic system. Here we review early literature describing the fundamental mechanisms of antipsychotic drug efficacy, highlighting mechanistic concepts that have persisted over time. We then reconsider the original framework for understanding antipsychotic efficacy in light of recent advances in our scientific understanding of the dopaminergic effects of antipsychotics. Based on these new insights, we describe a role for the dopamine transporter in the genesis of both antipsychotic therapeutic response and resistance. We believe that this discussion will help delineate the dopaminergic nature of antipsychotic treatment resistant schizophrenia.